EBA's capital exercise and technical efficiency of the banks - Adhiraj Singh Rathore (Review of Economic Analysis (REA), 2020)
This study uses a sample of 194 banks from 15 EU countries and two-stage data envelopment analysis (DEA) to provide evidence on the impact of the European Banking Authority (EBA)'s capital exercise on banks' efficiency. In the first stage of the analysis, we measure the efficiency by employing DEA. We then use Tobit regression to investigate the impact of the capital exercise on banks' technical efficiency. We estimate several specifications while controlling for bank-specific attributes and country-level characteristics accounting for macroeconomic conditions, financial development and market structure. The results indicate that EBA's capital exercise came, as a shock for the banks would be contributing towards making the banks more stable. It would be preventing banks from excessive risk-taking activities. Furthermore, it would be allowing the banks to withstand the financial distress and contributing in banks be- coming less prone to the systemic risk. The study finds that the capital requirements would be creating favourable economic conditions, which would be, affect the extent, depth and quality of financial intermediation and banking services.
Keywords: G21; C67; 330; Eciency; Bank; Euro Area; DEA; Capital